Ectopic breast tissue lesion in axilla: Cytology report of two cases. Issue 8 (11th April 2019) - Nigam, Jitendra Singh; Garg, Pooja; Talukder, Shibojit
Abstract: Ectopic breast tissue (EBT) predominantly seen along the primitive embryonic milk lines that extend from axilla to groin. Axillary breast tissue is one of the common variant of EBT seen in 2% to 6% of women. Phyllodes tumour in EBT is uncommon. The various cystic, inflammatory and neoplastic lesions may occur in EBT similar to breast counterpart. Therefore, EBT should be carefully investigated as it may affect the management of the patient. We report two cases (axillary phyllodes tumour and axillary fibroadenoma) of axillary EBT diagnosed on cytology.